Charcoal production and household welfare in Uganda: a quantile regression approach - Ainembabazi, John H.; Shively, G.E.; Angelsen, A. (Cambridge University Press, 2013)
Previous research suggests that forest-dependent households tend to be poorer than other groups, and that extreme reliance on forest resources might constitute a poverty trap. We provide an example in which a non-timber forest product – charcoal – appears to be providing a pathway out of poverty for some rural households in Uganda. Data come from households living adjacent to natural forests, some of whom engage in charcoal production. We use a semi-parametric method to identify the determinants of participation in charcoal production and a quantile regression decomposition to measure the heterogeneous effect of participation on household income. We find that younger households and those with few productive assets are more likely to engage in charcoal production. We also show that, as a result of their participation, charcoal producers are better off than non-charcoal producers in terms of income, even though they are worse off in terms of productive assets.